NSW system of marine protected areas. - New South Wales. Department of Primary Industries ([Orange, N.S.W.] : NSW Department of Primary Industries, 2019)
Map showing New South Wales Aquatic Reserves, Marine Parks, NSW Waters, National Park/Nature Reserves, IMCRA 4.0 (Integrated Marine and Coastal Regionalisation of Australia) bioregional boundaries and prominent cities along the coast line. Includes two ancillary maps. No relief shown.
[Inset 1] [Lord Howe Island Province] -- [Inset 2] Barrenjoey Head Aquatic Reserve to Shiprock Aquatic Reserve].
1 map with 2 ancillary maps.
Title devised by cataloguer.
Mode of Access: Available online.
Keywords: Aquatic parks and reserves -- Australia -- New South Wales -- Maps; Aquatic parks and reserves -- New South Wales -- Maps; Marine parks and reserves -- Australia -- New South Wales -- Maps; Marine parks and reserves -- New South Wales -- Maps; Aquatic parks and reserves; Marine parks and reserves; New South Wales -- Maps; New South Wales; Digital maps